Analysis Of Basic Teaching Skills Of A Prospective Math Teacher - Enika Wulandari; YL Sukestiyarno; Scolastika Mariani; Masrukan Masrukan (Universitas Negeri Semarang, 2022)
The prospective teacher's skills in teaching will determine what his teaching skills will be like when he becomes a teacher. This study aims to identify the basic teaching skills shown by a prospective teacher when carrying out teaching practice in the Micro Teaching course. This study uses a qualitative approach. The research subject was 1 prospective mathematics teacher who was carrying out teaching practice in Microteaching courses in the second semester of the 2021/2022 academic year. Data was collected through teaching practice video studies, interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model. The identification of basic teaching skills is guided by a theory about basic teaching skills. Checking the validity of the data is done by technical triangulation. The results showed that the subject 1) did not demonstrate questioning skills 2) demonstrated strengthening skills 3) demonstrated skills in variations in the form of variations in learning methods 4) demonstrated skills in explaining material, (5) demonstrated skills in opening and closing, 6) subjects did not practice small group discussions . 7) demonstrate classroom management skills, 8) demonstrate skills in organizing small group work.